2017
DOI: 10.1007/s10266-017-0302-9
|View full text |Cite
|
Sign up to set email alerts
|

The prominent proteins expressed in healthy gingiva: a pilot exploratory tissue proteomics study

Abstract: Gingiva is a unique tissue which protects the underlying periodontal tissues from consistent mechanical and bacterial aggressions. Molecular analysis of gingiva is likely to improve our understanding of the underlying biological processes at work. The aim of this preliminary exploratory study is to analyze the proteomic profile of healthy gingiva and to detect prominently expressed proteins. Gingival tissue samples were obtained from periodontally healthy individuals who underwent surgical crown lengthening pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 43 publications
0
19
1
Order By: Relevance
“…The entirety of proteomics findings has suggested that affected gingival tissue during progression contained a defense response that was regulated by many proteins and through various pathways and networks. Although we could not find any earlier data regarding the global quantitative proteome of mouse gingiva, the number of identified or quantified proteins in this study was considerably higher than that reported earlier in the human gingival tissue or the gingiva of mini pigs . The mouse genome reportedly encodes 48 709 genes, of which about one half are protein coding (22 018 genes) .…”
Section: Discussioncontrasting
confidence: 97%
See 2 more Smart Citations
“…The entirety of proteomics findings has suggested that affected gingival tissue during progression contained a defense response that was regulated by many proteins and through various pathways and networks. Although we could not find any earlier data regarding the global quantitative proteome of mouse gingiva, the number of identified or quantified proteins in this study was considerably higher than that reported earlier in the human gingival tissue or the gingiva of mini pigs . The mouse genome reportedly encodes 48 709 genes, of which about one half are protein coding (22 018 genes) .…”
Section: Discussioncontrasting
confidence: 97%
“…Usual protein isolations from gingival tissues have been performed using mechanical and biochemical disruption strategies, including freeze–thawing, homogenization, sonication, or bead beating . In the field of tissue proteomics, the pressure cycling technology (PCT), using a barocycler instrument, is one of the emerging sample preparation methods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…, Yaprak et al . ), but only three have studied the protein composition in cases of endodontic infections (Nandakumar et al . , Provenzano et al .…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, there are no data on 8-OHdG levels in tissues affected by peri-implantitis, therefore we could not compare our results with the literature. PARK7/DJ-1 was identified in the healthy gingiva,36 however, data on its role in peri-implant and periodontal diseases are unavailable. It has been demonstrated that PARK7/DJ-1 attenuates the expression of pro-inflammatory mediators in microglia and astrocytes 37.…”
mentioning
confidence: 99%